Metacognition and autonomy in building a community for language learning through VR digital gaming - Mark Feng Teng (Computers & Education: X Reality, 2024)
This paper delves into the vibrant domain of VR digital gaming through the critical lenses of metacognition and learner autonomy. It introduces an integrated framework designed to illuminate the interplay between these two pivotal concepts within the VR digital gaming environment. Central to this framework are distinct regulatory mechanisms that empower learners by allowing them to navigate and take control of their learning journeys. The framework interprets metacognitive processes from elements of adaptivity, control, and feedback, while exploring autonomy through the dimensions of location, formality, pedagogy, and locus of control. This framework is grounded in the recognition that enabling learners to exert control over their technologically mediated learning environments is a fundamental issue in building a language learning community. The paper not only sheds light on the theoretical underpinnings of metacognition and autonomy but also offers practical implications for their application in VR digital gaming. It delineates the evolving roles of teachers and learners within this dynamic educational landscape, highlighting how these roles are being reshaped to accommodate and leverage the affordances of VR digital gaming for enhanced language learning.